Удосконалення методики випробування та аналіз зносостійкості матеріалів в умовахзношування закріпленим абразивом - Попов, Сергій Миколайович; Антонюк, Дмитро Анатолійович (Eastern-European Journal of Enterprise Technologies, 2009)
There are presented results of work aimed at improvement of methods of test of materials at wear process by fixed concrete abrasive with the possibility of carrying out of researches in a wide range of factors variation. The complex of tests and analysis by definition of intensity of wear process standard wearproof deposited materials are spent.